2007
DOI: 10.1086/521605
|View full text |Cite
|
Sign up to set email alerts
|

A Period Study and Spot Model for the Eclipsing Binary TU Bootis

Abstract: ABSTRACT. We present the photometric properties of the eclipsing binary TU Boo from detailed studies of the period and light variations, based on our new BVR observations and historical data collected from the literature. A total of 349 times of minimum light over 80 yr, including our four timings, were used for the period study. An analysis of the resulting diagram reveals that the orbital period of TU Boo has varied in a quasi-sinusoidal O-C way superposed on a long-term period decrease. The secular variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…However, we failed to find any connection between the luminosity variation and the period change. V432 Per is the third of six cool binaries on our program which does not conform to a prediction of Applegate's mechanism (Kim et al 1997(Kim et al , 2003a(Kim et al , 2003bLee et al 2004Lee et al , 2007b. Hence, the sinusoidal component of the period variability most likely arises from the light-time effect due to a dM tertiary companion gravitationally bound to the V432 Per system.…”
Section: Cyclical Period Variationmentioning
confidence: 71%
See 1 more Smart Citation
“…However, we failed to find any connection between the luminosity variation and the period change. V432 Per is the third of six cool binaries on our program which does not conform to a prediction of Applegate's mechanism (Kim et al 1997(Kim et al , 2003a(Kim et al , 2003bLee et al 2004Lee et al , 2007b. Hence, the sinusoidal component of the period variability most likely arises from the light-time effect due to a dM tertiary companion gravitationally bound to the V432 Per system.…”
Section: Cyclical Period Variationmentioning
confidence: 71%
“…We can see that a large, dark spot on the primary star and its variability has been sufficient for the light-curve representations of V432 Per at the two different times. It is possible that the intrinsic light variations of the binary system could be caused by the simultaneous existence of the magnetic cool spot on the primary star and a hot spot due to mass transfer between the components (e.g., TU Boo, Lee et al 2007b). However, separate trials for such spot configurations did not give a better fit than our single, cool-spot model.…”
Section: Light-curve Synthesismentioning
confidence: 99%
“…The magnitude differences of the comparison star (C) minus that of the check star (CH) are shown in the lower part of Figure 1. The distortions and O'Connell effect (Niarchos et al 1996;Lee et al 2007;Coughlin 2010) have been variable in the past, therefore we look forward to much more variations to investigation on the magnetic activities. However, the upper points of Figure 1 display the height of light curves in 2020 and 2021 are nearly the same and symmetric with total eclipse, maybe the activities on the surface of the components are weak.…”
Section: Observationsmentioning
confidence: 99%
“…The effective temperature of the secondary component is 5805 K, slightly higher than the primary component 5800 K. According to the definitions of A-subtype and W-subtype (Binnendijk 1970), although the difference of temperature is very small, the primary one should be the hotter stars for A-type contact binaries. Lee et al (2007) also made the same way to reveal that it is an typical A-type system with q = 0.508, T 1 = 5800 K, T 2 = 5737 K. However, via the fitting of UBVRI-band light curves, Coughlin (2010) suggested that TU Boo is a near-contact or barely semidetached system with q = 0.481, T 1 = 5821 K, T 2 = 5691 K. In these investigations, their asymmetric light curves were fitting with the different spot. Did the spot make influence on the structure?…”
Section: Photometric Solutions With the Wilson-devinney Programmentioning
confidence: 99%
See 1 more Smart Citation